2004
DOI: 10.1162/003465304323023769
|View full text |Cite
|
Sign up to set email alerts
|

Schooling and Parental Death

Abstract: Abstract-Loss of a parent is one of the most traumatic events a child can face. If loss of a parent reduces investments in children, it can also have long-lasting implications. This study uses parametric and seminonparametric matching techniques to estimate how one human capital investment, school enrollment, is affected by a parent's recent death. We analyze data from 600,000 households from Indonesia's National Socioeconomic Survey (Susenas) during 1994-1996. We nd a parent's recent death has a large effect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
105
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(111 citation statements)
references
References 26 publications
5
105
1
Order By: Relevance
“…In a related literature, some influential studies investigate the effect of that extreme form of health shock which is parental death. Gertler et al (2004) use three repeated crosssections of household data from Indonesia to test how the loss of a parent affects investment in children. They find that a parent's recent death has a large effect on the child's school enrollment, irrespective of the gender of the child and of the parent who dies.…”
Section: Background Literature and Our Main Contributionmentioning
confidence: 99%
“…In a related literature, some influential studies investigate the effect of that extreme form of health shock which is parental death. Gertler et al (2004) use three repeated crosssections of household data from Indonesia to test how the loss of a parent affects investment in children. They find that a parent's recent death has a large effect on the child's school enrollment, irrespective of the gender of the child and of the parent who dies.…”
Section: Background Literature and Our Main Contributionmentioning
confidence: 99%
“…As married women become more involved in work activities located outside the home there will be a growing need to find a substitute to do important domestic work (cooking, cleaning, childcare, etc.). In the context of Ouagadougou, where there is a lack of public facilities for taking care of small children and a general unwillingness of men to participate in domestic activities, it may often be the case that the firstborn daughter is called upon to provide that work, with adverse consequences for her schooling (Gertler, Levine, and Ames 2004;Montandon and Sapru 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Two ways commonly used in the region are hiring a young maid or fostering in an older child to help with domestic work. Nonetheless, a number of studies have shown that, in the absence of the mother and without adequate child care policies, girls -and especially the oldest daughter -are often called upon to assume the maternal figure, with adverse effects on their schooling (Gertler, Levine, and Ames 2004;Montandon and Sapru 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Typically this has involved exploiting plausibly exogenous sources of variation in family structure through natural experiments or instrumental variables methods (Lang & Zagorsky, 2001;Gruber, 2004;Finlay & Neumark, 2010) and also accounting for unobserved heterogeneity through the use of individual fixed effects (Cherlin et al, 1991), sibling fixed effects (Ermisch et al, 2004;Evenhouse & Reilly, 2004) and propensity score matching (Gertler et al, 2004). After accounting for endogeneity issues, these studies tend to find that divorce does not deteriorate children's outcomes.…”
Section: Literature Reviewmentioning
confidence: 99%